1998
DOI: 10.7326/0003-4819-129-11_part_1-199812010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Community-Acquired Bacterial Meningitis: Risk Stratification for Adverse Clinical Outcome and Effect of Antibiotic Timing

Abstract: In persons with community-acquired bacterial meningitis, three baseline clinical features of disease severity predicted adverse clinical outcome and stratified patients into three stages of prognostic severity. Delay in therapy after arrival in the emergency department was associated with adverse clinical outcome when the patient's condition advanced to the highest stage of prognostic severity before the initial antibiotic dose was given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
216
5
11

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 428 publications
(240 citation statements)
references
References 39 publications
8
216
5
11
Order By: Relevance
“…and to the time of the onset of consciousness disturbance. We recognize that the definitions we used for the timing of appropriate antibiotic therapy are not 13 completely precise and that using hours, instead of days, would have been much more informative. Unfortunately, this is a retrospective study and precise data could not be obtained from the records of many patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and to the time of the onset of consciousness disturbance. We recognize that the definitions we used for the timing of appropriate antibiotic therapy are not 13 completely precise and that using hours, instead of days, would have been much more informative. Unfortunately, this is a retrospective study and precise data could not be obtained from the records of many patients.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of survivors suffer from long-term neurological sequelae (4). Various prognostic factors associated with adverse clinical outcome were reported so far (6)(7)(8)(9)12,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of suspected bacterial meningitis, the goal is to emergently initiate appropriate empiric antibiotic therapy, based on the age of the patient, the underlying disease status, and cerebrospinal fluid (CSF) Gram stain, if available. Retrospective cohort studies of patients with communityacquired bacterial meningitis have shown an increase in adverse outcomes when initiation of antimicrobial therapy is delayed following the initial visit to a physician or the emergency room (ER) [7]. This data is supported by 2 additional retrospective studies showing improved outcomes and decreased mortality in patients that receive antimicrobial therapy earlier in the course of the disease [8,9].…”
Section: Initial Clinical Presentationmentioning
confidence: 95%
“…A delay in the initiation of antimicrobial therapy can result in poor outcomes. Retrospective studies have shown that the median delay between time of arrival at the emergency department and antibiotic administration was 4 h, and poor outcomes were associated with delayed antimicrobial therapy [7]. Among patients with a worsening condition while waiting in the ER, delay in antimicrobial therapy longer than 6 h after arrival to the ER was associated with increased risk of death [22].…”
Section: Diagnosismentioning
confidence: 99%